2011
DOI: 10.1159/000332983
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Salt Water Soaks on Biophysical and Molecular Parameters in Psoriatic Epidermis Equivalents

Abstract: Background/Aims: The exact mechanisms of action of balneophototherapy are incompletely understood. We aimed to investigate the effect of salt water soaks on ultraviolet (UV) transmission and the expression of molecular parameters of psoriasis. Methods: We studied UV transmission and the expression of antimicrobial peptides and skin-derived antileukoproteinase (SKALP/elafin) in psoriatic epidermis equivalents which were pretreated with tap water and differently concentrated salt water solutions. Moreover, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 54 publications
0
26
3
Order By: Relevance
“…Some studies indicate that the main therapeutic effect of climatotherapy at the Dead Sea can be attributed primarily to the sunshine and secondarily to the hypersaline seawater . Other studies show that balneotherapy with Dead Sea salt solution soaks in combination with NB‐UVB therapy is superior to NB‐UVB therapy alone , which could be attributed to increased photosensitivity of the skin to UV radiation . We do not think that explains the results in our study for two reasons.…”
Section: Discussioncontrasting
confidence: 61%
“…Some studies indicate that the main therapeutic effect of climatotherapy at the Dead Sea can be attributed primarily to the sunshine and secondarily to the hypersaline seawater . Other studies show that balneotherapy with Dead Sea salt solution soaks in combination with NB‐UVB therapy is superior to NB‐UVB therapy alone , which could be attributed to increased photosensitivity of the skin to UV radiation . We do not think that explains the results in our study for two reasons.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, Gambichler et al . showed that high‐concentration salt solution significantly reduces antimicrobial peptides, like human beta defensin ‐ 2 (hBD‐2), that are usually over‐expressed in psoriasis, and it also decreases skin‐derived antileukoproteinase (SKALP/elafin), found in numerous inflammatory skin diseases .…”
Section: Discussionmentioning
confidence: 99%
“…10 This commercially available ELISA kit is designed to measure the concentration of hBD2 from human serum/plasma, or conditioned medium. The concentration of hBD2 was determined based on the standard curve.…”
Section: Elisamentioning
confidence: 99%